Respuestas

  • Usuario de Brainly
2013-10-30T02:04:26+01:00

 (3x-4y= 41)*(6)  entonces 18x-24y=246
(11x+6y=47)*(4)                44x+24y=188  sumamos
                                      ----------------------
                                      62x=434
                                            
                                         x=434/62
                                         x=7

remplazando en. 3x-4y=41.  es iguala. 3*7-4y=41 esto es igual a. 21-4y=41

-4y=41-21.   
-4y=20
 y=20/-4=-5